Analysis Of Supply Materialsseal Processing Manufacturing Companies (Case Study of PT. Inti Nusa Raya Indonesia in Laeya Village South Poleang Subdistrict, Bombana Regency) - Niluh Eva Aryanti; Ine Fausayana; Yusna Indarsyih (International Journal of Technology and Education Research, 2024)
This study aims to determine the raw material inventory process at the seaweed manufacturing company PT Inti Nusa Raya Indonesia in Laeya Village, South Poleang District, Bombana Regency. The main focus of this research is to determine the amount of seaweed processing raw material inventory using the Economic Order Quantity (EOQ) method. The research object was selected using purposive sampling technique with the main respondents being the production manager and accountant of PT Inti Nusa Raya Indonesia. Data was collected through interviews and literature studies, then analyzed using the EOQ method which includes annual order costs, annual storage costs, optimal order quantities, total costs, reorder points, estimated order quantities throughout the year (N), and estimated inter-order times (T). The results showed that the company PT Inti Nusa Raya Indonesia uses two types of raw materials in its production process, namely Eucheuma cottonii and Eucheuma spinosum seaweed. The company obtains raw materials through cooperatives or directly from farmers at a price of Rp 17,000/Kg for Eucheuma cottonii and Rp 6,000/Kg for Eucheuma spinosum, with a minimum dryness requirement of 30%. The use of the EOQ method allows the company to save the cost of Eucheuma cottonii raw material inventory by 79.67% and Eucheuma spinosum by 80.23% compared to the company's conventional method